1994
DOI: 10.1080/09670269400650431
|View full text |Cite
|
Sign up to set email alerts
|

AHydrodictyon reticulatumbloom at Loe Pool, Cornwall

Abstract: An extensive bloom of Hydrodictyon reticulatum was observed on Loe Pool, a eutrophic coastal freshwater lake in Cornwall. In previous years the Pool has experienced cyanobacterial blooms, but in 1993 Hydrodictyon became dominant for the first time. It was estimated that approximately 24% of the Pool was covered by Hydrodictyon and dissolved oxygen saturations were observed to range between 220% and 34% within a mat of Hydrodictyon. The reason for the shift in algal dominance remains unclear, though large numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…in situ) produced 6-methyl brGDGTs. Similar contributions of 6-methyl brGDGTs, and thus higher IR, were also observed in suspended particulate matter from the Yenisei River (De Jonge et al, 2014a), and upstream of the Iron Gates in the Danube River, where the higher IR was coupled to in-river production facilitated by the lower flow velocity and decreased turbidity of the river water (Freymond et al, 2017). Hence, the significantly higher IR in combination with the higher Cnormalized concentrations of brGDGTs in the Carminowe creek sediments suggests that the brGDGT signal is mainly aquatic.…”
Section: Tracing Brgdgts From Soils To Creek Bed Sedimentssupporting
confidence: 55%
See 1 more Smart Citation
“…in situ) produced 6-methyl brGDGTs. Similar contributions of 6-methyl brGDGTs, and thus higher IR, were also observed in suspended particulate matter from the Yenisei River (De Jonge et al, 2014a), and upstream of the Iron Gates in the Danube River, where the higher IR was coupled to in-river production facilitated by the lower flow velocity and decreased turbidity of the river water (Freymond et al, 2017). Hence, the significantly higher IR in combination with the higher Cnormalized concentrations of brGDGTs in the Carminowe creek sediments suggests that the brGDGT signal is mainly aquatic.…”
Section: Tracing Brgdgts From Soils To Creek Bed Sedimentssupporting
confidence: 55%
“…the Congo River, Weijers et al, 2007b;Hemingway et al, 2017; or the Amazon River, Kim et al, 2012), or have experienced a recent episode of extreme rainfall (e.g. the Danube River, > 100 mm in 3 d causing a 100year flood event, Freymond et al, 2017; or the Rhône River, with heavy rainfall during sampling; Kim et al, 2015). The Carminowe creek area does not have a clear rainy season and is further characterized by its limited relief.…”
Section: Tracing Brgdgts From Soils To Creek Bed Sedimentsmentioning
confidence: 99%
“…Hillebrand (1983) recorded daytime differences in three waterbodies of 1-6°C at the surface in comparison with below metaphyton mats dominated by different filamentous algal species. Depth-related trends in dissolved oxygen, which remained at or above 100% saturation at the surface for the first 7 weeks in the present study but became progressively under-saturated within the mat beginning with the third week, were similar to results of Flory & Hawley (1994), who also reported rapid diel oxygen fluctuation within the mat interior. The fine-scale physicochemical gradients can be expected to affect not only metaphyton condition and community structure (considered below), but other metaphyton-associated organisms as well (Barker, Irfanullah & Moss, 2010).…”
Section: Physicochemical Environmentsupporting
confidence: 88%
“…As these mats proliferate, their influence over surrounding waters increases, resulting in the potential for large shifts between supersaturated DO during daylight and anoxic conditions at night. Flory and Hawley (1994) linked Hydrodictyon blooms with diurnal DO fluctuations between 34% and 200% saturation in a coastal freshwater lake, while Morgan et al (2006) reported that 64% of the variance in diurnal DO within agricultural streams in Illinois was explained by filamentous algal biomass, primarily Cladophora. Flory and Hawley (1994) linked Hydrodictyon blooms with diurnal DO fluctuations between 34% and 200% saturation in a coastal freshwater lake, while Morgan et al (2006) reported that 64% of the variance in diurnal DO within agricultural streams in Illinois was explained by filamentous algal biomass, primarily Cladophora.…”
Section: Dissolved Oxygen and Phmentioning
confidence: 99%